New index using triglyceride glucose-body mass index for predicting mortality in patients with antineutrophil cytoplasmic antibody-associated vasculitis - Park, Pil Gyu; Pyo, Jung Yoon; Ahn, Sung Soo; Song, Jason Jungsik; Park, Yong-Beom; Huh, Ji Hye; Lee, Sang-Won (Frontiers in Medicine, 2023)
Background This study aimed to investigate whether triglyceride glucose-body mass index (TyG-BMI) and a new index using TyG-BMI (NITGB) could predict all-cause mortality in non-obese patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). Methods The medical records of 78 non-obese AAV patients (BMI < 23.0 kg/m2 for Asians) were retrospectively reviewed. TyG-BMI was calculated by the equation: Ln (triglyceride × fasting glucose/2) × BMI. To develop NITGB, we assigned a weight of a number close to an 0.1 decimal integer to each variable according to the slopes for independent variables with P-value < 0.1 in the multivariable Cox analysis. Results The median age was 54.3 years and five patients died. When non-obese AAV patients were divided into two groups based on TyG-BMI ≥ 187.74, those with TyG-BMI ≥ 187.74 exhibited a significantly higher risk for all-cause mortality than those without (RR 9.450). Since age (HR 1.324), Birmingham vasculitis activity score (BVAS; HR 1.212), and TyG-BMI ≥ 187.74 (HR 12.168) were independently associated with all-cause mortality, NITGB was developed as follows: age + 0.2 × BVAS + 2.5 × TyG-BMI ≥ 187.74. When non-obese AAV patients were divided into two groups based on NITGB ≥ 27.36, those with NITGB ≥ 27.36 showed a significantly higher risk for all-cause mortality than those without (RR 284.000). Both non-obese AAV patients with TyG-BMI ≥ 187.74 and those with NITGB ≥ 27.36 exhibited significantly higher cumulative rates of all-cause mortality than those without. Conclusion NITGB along with TyG-BMI could predict all-cause mortality in non-obese AAV patients.